SPECIAL NEEDS SCHOOL WITH GREEN-UNIVERSAL DESIGN CONCEPT IN BOGOR REGENCY - Ananda Leoni Nurusyifa (Architecture Study Program, Department of Civil Engineering, Faculty of Engineering, Universitas Negeri Semarang, Indonesia, 2023)
Bogor Regency is included in The Province of West Java which has the highest amount of children with special needs (disability) in Indonesia. Based on the indication of National Economic Survey Data (SUSENAS), by the year 2018, 3 of 10 children with disability never really attend formal study at school. Until 2019, the number of children with disability that never attended school reach 400,000 children. One of the causes of many children with disability never attending school is that they are indicated as the 40% poorest families in Indonesia. Other than financial problems, the lack of learning facilities like special needs schools is also becoming the cause of many children with disability never really attending school life. The number of special needs schools in 2019 is only 1.861 in Indonesia. That is inversely proportional to the number of children with disability that reach the number 500,000 children by the year 2019. Special needs school is a learning facility for children with certain disabilities. Special needs school is made as a place for children with disabilities to study and improve their certain interests and talent just like normal children did. The building of special needs school is expected to be a place that can be used by the user without exception. The application of a universal design concept is suitable for special needs school buildings. Other than that, the application of green architecture is also needed to create a good environment.